Pathways and Consequences of Legal Irregularity Senegalese Migrants in France, Italy and Spain - Vickstrom, Erik R. (IMISCOE Research Series,, 2019)
This open access book provides a unique study of the complexities and consequences of irregular legal status of Senegalese migrants in Europe. It employs sophisticated quantitative methods to analyze unique life-history data to produce policy-relevant conclusions. Using the MAFE dataset as empirical evidence, the book focuses on the legal paths of Senegalese migrants in three different European countries. It shows how multiple contexts of reception produce pathways into irregular legal status and how the resulting complex configurations of irregular status shape migrants' economic integration into their host societies as well as their ongoing participation in the development of their sending societies. The book thereby increases our understanding of the functioning of African migration systems and the corresponding inclusion patterns in Europe. As such this book will be of interest to scholars working in migration studies, policy makers, and legalprofessionals.